BALINESE LANGUAGE POLICY: THE USE OF LANGUAGE SIGNS IN PUBLIC SPACES - Yendra Yendra; Ketut Artawa (LLDIKTI Wilayah X, 2025)
The increasing influence of multiculturalism and multilingualism, together with the expansion of tourism in Bali, has significantly contributed to the decline in the number of Balinese language speakers. To address this issue and to strengthen the sustainable use and preservation of the Balinese language and script, the government enacted Bali Governor Regulation Number 80 of 2018, known as the Balinese Language Policy. This study examines how this policy is put into practice through language signs in public places, often called the Linguistic Landscape (LL). The analysis specifically focuses on Article 6 paragraph (1) of the regulation, which mandates that Balinese script be placed above Latin letters in the naming of Hindu places of worship, traditional institutions, commemorative inscriptions, government and private buildings, streets, tourism facilities, and other public amenities. Employing a qualitative descriptive approach, the study involves an empirical survey of language signs in public spaces, their categorization, and analysis of policy implementation. Within the Balinese linguistic landscape, signs are classified as public and personal. The findings indicate that the Balinese Language Policy has been effectively implemented on public signage in accordance with the regulation. However, its implementation on personal signage remains limited, as only some individuals have adopted the policy